Evaluation of Internship Programs for the Preservice Teachers in Economics and Business: A Kirkpatrick Four-level Model - Muhammad Bukhori Dalimunthe; Danny Ajar Baskoro; Riza Indriani; Mohammad Zuber Abd Majid; Siti Chairani Lubis (Jurnal Pendidikan Ekonomi, 2024)
This study aimed to evaluate an internship programme for preservice teachers. The program evaluation model uses the Kirkpatrick Model which consists of four levels: reaction, learning, behaviour, and outcome. This model is suitable for evaluating internship programmes in reviewing the development of preservice teachers from the initial level to the completion of the internship programme targets. This study involved prospective teachers (n=205) in Economics and Business at the Universitas Negeri Medan. Data were collected online using a Google Forms questionnaire over two months in 2022. Data analysis used quantitative description to explore the programme achievements at each level in depth. The findings showed that the mean of reaction (5.05), learning (5.20), behaviour (4.96), and outcome (5.03) were above the ideal mean of 3.50. Internship programme participants have met the average achievement target of Kirkpatrick's four-level model, where learning evaluation is more meaningful for student teachers when participating in the internship programme compared to other levels. Overall, with this research, it is hoped that internship programme managers can design more targeted and measurable programmes to improve the experience of prospective teachers.  Keywords: internship program, preservice teacher, evaluation, Kirkpatrick four-level